A networked-hutong siwei for developing Australia's pedagogical strategy for International Research Education: intellectual interconnectedness and theoretical alternatives. Issue 3 (3rd April 2023) - Meng, Hui; Qi, Jing; Leng, Derong
ABSTRACT: Although 30% of international students who study in Australia are from China, there is a well-documented intellectual silence of Chinese students, the in-class silence of Chinese students in coursework degrees in particular. In response to the national policy and to provide insights into the international research education of Australia, this article reports on a study that examines the intellectual silence of research students from China enrolled in Master's or doctoral degrees in five Australian universities. This qualitative study analysed semi-structured interviews with Australian research supervisors and Chinese research students, as well as research theses produced by Chinese research students. The intellectual silence of Chinese research students is examined through the lens of Qi's concept – networked-hutong siwei. The results show that to adopt the networked-hutong siwei could provide a new perspective to reconsider the intellectual silence of Chinese research students by enhancing international students' epistemological awareness of the interconnectedness of different intellectual resources and thus seeking theoretical and conceptual alternatives.